(untitled) (Global Journals of Research in Engineering, 2011)
The name "WiMAX" was created by the #x201C;WiMAX Forum#x201D;, which was formed in June. WiMAX (Worldwide Interoperability for Microwave Access) standards define formal specifications for deployment of broadband wireless metropolitan area networks (wireless MANs).Wireless MANs as needed in WiMAX standards provide wireless broadband access anywhere, anytime, and on virtually any device. Introducing the various type of scheduling algorithm, like FIFO,PQ,WFQ, for comparison of four type of scheduling service, with its own QoS needs and also introducing OPNET modeler support for Worldwide Interoperability for Microwave Access (WiMAX) network. The simulation results indicate the correctness and the effectiveness of theses algorithm. This paper presents a WiMAX simulation model designed with OPNET modeler 14 to measure the delay, load and the throughput performance factors.